Classroom behavior of Maranaw Muslim high school students of the Jamiatul Philippines Al-Islamia during the month of Ramadan and implications for educational administration and supervision - Rabara, Sabina R. 1943- (s.n.], 1968)
The author surveyed the classroom behavior of high school students of the Jamiatul Philippine Al-Islamia during the month of Ramadan; and its implications on educational administration and supervision are sought in an attempt to provide the teachers a better understanding and appreciation of the practices of their Muslim students.